Impact of early life shocks on educational pursuits–Does a fade out co-exist with persistence? - Dhamija, Gaurav; Sen, Gitanjali (PloS one, 2022)
Changes in climatic conditions have increased the variability in rainfall patterns worldwide. A negative rainfall shock faced by children in the initial 1000 days of life and the resulting malnutrition can harm the likelihood of children's survival, overall growth, development of the brain, motor skills, and cognitive abilities, leading to poor performance in education and labor market. While the existing findings about the long-run outcomes are mixed, it is essential to understand the nuances in such an estimation. Using the exogenous variation in rainfall in India, we estimate the impact of adverse shocks at birth on the cognitive abilities of children at ages 5, 8, 12, and 15, on educational attainments, and the likelihood of studying STEM at higher secondary school. The Young Lives Survey data from Andhra Pradesh, India, presents evidence of the negative impact of rainfall shocks at birth on cognitive abilities from age 5 to 8, attenuating at age 12. Using nationally representative data, while we investigate the impact of adverse rainfall shocks at birth on academic performance measured by the high school grades and STEM choice at higher secondary school, we do not find a persistent impact. We unfold the impact of rainfall shocks on a chain of outcomes connected to long-run educational pursuits, as it helps to identify the most crucial stage for policymaking. Since STEM subjects are strongly associated with the labor market, connecting the association with early life shocks seems to be an essential addition to the literature. While we find evidence of reduced cognitive abilities in the early years, those do not seem to persist in the long run. The potential sample selection or attrition biases and the estimates of those biases can explain the nuances of estimating the long-run impact of adverse shocks at birth.